Preparation and evaluation of delayed release aceclofenac microspheres - Radhika, Parasuram Rajam; Luqman, Moidutty; Borkhataria, Chetan Hardas (Asian Journal of Pharmaceutics (AJP), 2014)
Delayed release microspheres of aceclofenac were formulated using an enteric polymer, cellulose acetate phthalate (CAP) prepared by solvent evaporation technique. The effects of various other modern enteric polymers such as hydroxyl propyl methyl cellulose phthalate (HPMCP), Eudragit L 100, and Eudragit S -100 on the release of aceclofenac from the CAP microspheres have been evaluated.The microspheres were characterized for particle size, scanning electron microscopy (SEM), percentage yield, drug entrapment, and for in-vitro release kinetics. The shape of microspheres was found to be spherical by SEM. The drug entrapment efficiency of microspheres was found to be ranging from 75.65 to 96.52 %w/w. The study was designed in the form of a factorial design in which the effects of HPMCP, Eudragit L 100, and Eudragit S 100 on the release rate of drug from CAP delayed release microspheres were evaluated. The results revealed that the HPMCP exhibits positive influence whereas Eudragit L 100 and Eudragit S 100 exhibits negative effect on the drug release rate of CAP microspheres. In vitro drug release from all formulations followed the first order release kinetics and erosion plot. Formulation with drug: CAP : HPMCP ratio of 1:8:2 was considered best because it showed delayed release.